Self-Reported Maternal Parenting Stress From 9 m Is Longitudinally Associated With Child ADHD Symptoms at Age 12: Findings From a Population-Based Birth Cohort Study - Endo, Kaori; Stanyon, Daniel; Yamasaki, Syudo; Nakanishi, Miharu; Niimura, Junko; Kanata, Sho; Fujikawa, Shinya; Morimoto, Yuko; Hosozawa, Mariko; Baba, Kaori; Oikawa, Nao; Nakajima, Naomi; et al. (Frontiers in Psychiatry, 2022)
Background: Attention-deficit/hyperactivity disorder (ADHD) develops in early childhood and carries lifelong impact, but early identification and intervention ensure optimal clinical outcomes. Prolonged or excessive parenting stress may be a response to infant behavioral differences antecedent to developmental disorders such as ADHD, and therefore represents a potentially valuable inclusion in routine early-life assessment. To investigate the feasibility of using routinely-collected self-reported maternal parenting stress as a risk marker for child ADHD, this study investigated the longitudinal association between maternal parenting stress from 1-36 months after childbirth and child ADHD in early adolescence. Methods: The sample comprised 2638 children (1253 girls) from the Tokyo Teen Cohort population-based birth cohort study. Mothers recorded parenting stress five times from 1-36 months following childbirth in the Maternal and Child Health Handbook, a tool used for routine early-life assessment in Japan. Nine years later, mothers evaluated their child’s ADHD symptoms at 12y using the hyperactivity/inattention subscale from the Strength and Difficulties Questionnaire. Results: Approximately 7.5% of parents reported that they had parenting stress at 36m after childbirth. 6.2% of children were evaluated as above the cut-off for ADHD symptoms at 12y. Parenting stress at 1m and 3-4m was not associated with child ADHD symptoms at 12y. However, child ADHD symptoms at 12y was significantly associated with parenting stress at 9-10m (unadjusted OR = 1.42, p = .047, 95% CI [1.00, 2/00]), 18m (unadjusted OR = 1.57, p = .007, 95% CI [1.13, 2.19]) and 36m (unadjusted OR = 1.67, p = .002, 95% CI [1.20, 2.31]). These associations remained after adjustment for child’s sex, age in months and family income. Conclusions: We identified associations between parenting stress at 9-10m, 18m and 36m after childbirth and child ADHD symptoms at 12 years old. Self-reported parenting stress data may have utility as an early indicator for ADHD risk. Participation in early-life health checks, assessment of parenting stress, and tailoring support to family needs should be promoted for early identification and intervention for ADHD.